Incidence of vasovagal syncope among blood donors – experiences from a Norwegian blood bank - Dorthe Charlotte Johannessen; Sadaf Nabi Bhatti; Abid Hussain Llohn; Seyed Ali Mousavi (Bioingeniøren, 2023)
Background/ objective: Vasovagal reactions related to blood donation are often mild or moderate, but severe reactions such as syncope can occur. This study sought to investigate the incidence of syncope among blood donors in a Norwegian blood bank and to examine whether demographics and the timing of donation influenced the syncopal reactions experienced by donors.